2022
DOI: 10.3389/fneur.2022.977307
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of glucose metrics during the early brain injury period after aneurysmal subarachnoid hemorrhage: An opportunity for continuous glucose monitoring

Abstract: Hyperglycaemia, hypoglycaemia and higher glucose variability during the Early Brain Injury (EBI) period of aneurysmal subarachnoid hemorrhage (aSAH) have been associated with poor clinical outcome. However, it is unclear whether these associations are due to direct glucose-driven injury or if hyperglycaemia simply acts as a marker of initial severity. Actually, strict glucose control with intensive insulin therapy has not been demonstrated as an effective strategy for improving clinical outcomes after aSAH. Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…Furthermore, glycemic variability was found to be associated with cerebral metabolic distress (defined as lactate/pyruvate ratio >40), as well as hospital mortality, after subarachnoid hemorrhage [ 96 ]. On the other hand, a recent study emphasized that it was still partially unclear whether the association between glycemic variability and brain dysfunction following subarachnoid hemorrhage was due to direct deleterious effects induced by glucose dysregulation or if hyperglycemia was an epiphenomenon related to initial bleeding severity [ 97 ]. The study concluded that further research was needed to understand the most appropriate and informative timing for glucose monitoring and how to combine different glucose metrics with markers of brain injury [ 97 ].…”
Section: Future Applications—adding Continuous Glucose Monitoring And...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, glycemic variability was found to be associated with cerebral metabolic distress (defined as lactate/pyruvate ratio >40), as well as hospital mortality, after subarachnoid hemorrhage [ 96 ]. On the other hand, a recent study emphasized that it was still partially unclear whether the association between glycemic variability and brain dysfunction following subarachnoid hemorrhage was due to direct deleterious effects induced by glucose dysregulation or if hyperglycemia was an epiphenomenon related to initial bleeding severity [ 97 ]. The study concluded that further research was needed to understand the most appropriate and informative timing for glucose monitoring and how to combine different glucose metrics with markers of brain injury [ 97 ].…”
Section: Future Applications—adding Continuous Glucose Monitoring And...mentioning
confidence: 99%
“…On the other hand, a recent study emphasized that it was still partially unclear whether the association between glycemic variability and brain dysfunction following subarachnoid hemorrhage was due to direct deleterious effects induced by glucose dysregulation or if hyperglycemia was an epiphenomenon related to initial bleeding severity [ 97 ]. The study concluded that further research was needed to understand the most appropriate and informative timing for glucose monitoring and how to combine different glucose metrics with markers of brain injury [ 97 ]. The importance of selecting the most appropriate metrics for CGM data analysis for the study of brain function was also indicated in another recent study, which showed that, in T2DM patients, the glucose coefficient of variation (CV) and time below range (TBR) were not associated with any of the investigated aspects of cognitive function [ 98 ].…”
Section: Future Applications—adding Continuous Glucose Monitoring And...mentioning
confidence: 99%
“…[11]. Although some pilot studies have observed the association between acute GV and clinical outcomes in patients with ICH [10,[17][18][19][20][21][22][23], the results were not consistent [24]. Therefore, in this study, we performed a meta-analysis to systematically evaluate the association between acute GV and prognosis in patients with ICH.…”
Section: Introductionmentioning
confidence: 95%